2021
DOI: 10.1155/2021/6626150
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Surgery Consultations in COVID-19 Critically Ill Patients: Beyond Conservative Approach

Abstract: Introduction. Iatrogenic pneumothoracis, barotraumas, and tracheoesophageal fistulae, especially after prolonged intubation, and tracheal stenosis are all entities involving thoracic surgeons’ consultation and management. With the surge of COVID-19 cases particularly in the critical care settings, various types of complications have been observed that require intervention from thoracic surgeons. Methods and Materials. A retrospective study was conducted in an academic healthcare institute in the Eastern Provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, most patients with isolated PM or accompanying PM were followed up without an intervention. Although some studies showed a survival benefit for interventions in patients with PTX in COVID-19 patients, a study comparing COVID-19 patients with PTX and pleural effusion to non-COVID-19 patients showed that the benefit of tube thoracostomy was more limited in the former [ [68] , [69] , [70] ]. There is no consensus regarding the treatment of PTX/PM in COVID-19 patients yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients with isolated PM or accompanying PM were followed up without an intervention. Although some studies showed a survival benefit for interventions in patients with PTX in COVID-19 patients, a study comparing COVID-19 patients with PTX and pleural effusion to non-COVID-19 patients showed that the benefit of tube thoracostomy was more limited in the former [ [68] , [69] , [70] ]. There is no consensus regarding the treatment of PTX/PM in COVID-19 patients yet.…”
Section: Discussionmentioning
confidence: 99%
“…patients or small sample size. 5,36 The ability to predict who may need a higher level of care may aid in clinical decision-making such as degree of patient monitoring (i.e. remote home monitoring versus admission).…”
Section: Discussionmentioning
confidence: 99%
“…There are many potential roles for thoracic surgeons during a respiratory-symptom predominant viral pandemic. Certain complications of COVID-19 may require thoracic surgical intervention, including pneumothorax, pneumatocele, empyema, hemothorax, and end stage lung disease (5)(6)(7)(8). Given their clinical familiarity with the airway, thoracic surgeons may be called on to perform tracheostomies.…”
Section: Introductionmentioning
confidence: 99%